Docking, Synthesis and Evaluation of 4-hydroxy-1-phenyl-2(1H)-quinolone Derivatives as Anticancer Agents - Tendulkar, Chaitali P.; Dessai, Prachita Gauns; Mamle Desai, Shivlingrao; Kadam, Amrita (Current Drug Discovery Technologies, 2024)
Background: The estimated number of cancer cases in India for the year 2022 was found to be 14,61,427. The development of chemotherapeutic agents has reduced the mortality rate, however, they have high toxicity which is a disadvantage. Many researchers have found out that quinolin-2- one possesses anticancer activity, with this background we thought of synthesizing the quinolin-2-one derivatives. Objective: This study aimed to carry out docking, synthesis, characterization, and evaluation of 2-(2- (4-Hydroxy-2-oxoquinolin-1(2H)-yl)phenyl/ substituted phenyl)-3-(phenylamino) thiazolidon-4-one derivatives (IVa-g) as an anticancer agent. Method: Diphenylamine and malonic acid treated with phosphoryl chloride gave compound I, which on formylation afforded compound II, which on reaction with various substituted aromatic phenylhydrazine derivatives gave compounds IIIa-g, which on further reaction with thioglycolic acid and anhydrous zinc chloride yielded the compounds IVa-g. Result: Among all the synthesized novel derivatives, compounds IV a-d showed 50% lysis in the IC50 range of 25-50μg for the A549 cell line, and compounds IVa, and IVb showed 50% lysis in the IC50 range of 25-50μg for the MDA-MB cell line. The compound, 3-((4-fluorophenyl)amino)-2-(2-(4- hydroxy-2-oxoquinolin-1(2H)-yl)phenyl)thiazolidin-4-one (IVg) was found to be the most active against both the cell line, A549 and MDA-MB with IC50 value of 0.0298μmol and 0.0338μmol respectively. The docking results revealed that the synthesized compounds exhibited well-conserved hydrogen bonding with one or more amino acid residues in the active pocket of EGFR tyrosine kinase domain with 4-anilinoquinazoline inhibitor erlotinib (PDB ID:1M17). Compound IVg showed the highest MolDock score of -137.813 compared to the standard drug Imatinib having a MolDock score of -119.354. Conclusion: Compound IVg showed the highest MolDock score and was also found to be most potent against both the cell line, A549, and MDA-MB.
Keywords: imatinib